Optimization of Hot Press Temperature and Eggshell Filler Composition in Biocomposite Fabrication Using the Taguchi Method - Intan Nazwa; Sunardi; Imron Rosyadi; Deni Purnomo; Erny Listijorini (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
The utilization of biomass waste as a reinforcing agent for biocomposites presents an attractive alternative in the development of environmentally friendly materials. This study aims to analyze the effect of varying percentages of chicken eggshell and crumb rubber fillers, as well as the hot press temperature, on the mechanical properties of the biocomposite, including the Modulus of Rupture (MOR), Modulus of Elasticity (MOE), and strain. The Taguchi method with an L9 orthogonal array design was employed to evaluate the effect of each factor and determine the optimum process combination. The research findings indicate that a 10% filler concentration yielded the highest stiffness, while a 20% filler concentration resulted in the largest strain value and demonstrated the best balance between strength and flexibility. A temperature of 170°C emerged as the most stable condition for most mechanical parameters, whereas a temperature of 190°C provided an increase in strength at higher filler compositions. From this study, it was ascertained that the optimal parameters are a 20% filler concentration and a temperature of 170°C (N1), yielding MOR, MOE, and strain values of 1473.53 MPa, 1186 MPa, and 2.86%, respectively. These findings affirm the critical importance of controlling the filler composition and processing parameters in producing biocomposites that are consistent and high-performing.